2023
DOI: 10.3390/polym15143064
|View full text |Cite
|
Sign up to set email alerts
|

Application of Green Polymeric Nanocomposites for Enhanced Oil Recovery by Spontaneous Imbibition from Carbonate Reservoirs

Yaser Ahmadi,
Mohamed Arselene Ayari,
Meysam Olfati
et al.

Abstract: This study experimentally investigates the effect of green polymeric nanoparticles on the interfacial tension (IFT) and wettability of carbonate reservoirs to effectively change the enhanced oil recovery (EOR) parameters. This experimental study compares the performance of xanthan/magnetite/SiO2 nanocomposites (NC) and several green materials, i.e., eucalyptus plant nanocomposites (ENC) and walnut shell ones (WNC) on the oil recovery with performing series of spontaneous imbibition tests. Scanning electron mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The common types of nanoparticles used in EOR technology can be categorized as metal and its oxide nanoparticles [ 22 , 23 , 24 ], inorganic nanoparticles [ 25 , 26 , 27 , 28 , 29 ], and organic nanoparticles [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. In his research, Shah [ 22 ] found that metal nanoparticles can reduce the viscosity of crude oil and can be used in thick oil extraction.…”
Section: Introductionmentioning
confidence: 99%
“…The common types of nanoparticles used in EOR technology can be categorized as metal and its oxide nanoparticles [ 22 , 23 , 24 ], inorganic nanoparticles [ 25 , 26 , 27 , 28 , 29 ], and organic nanoparticles [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. In his research, Shah [ 22 ] found that metal nanoparticles can reduce the viscosity of crude oil and can be used in thick oil extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmadi et al used green polymeric nanocomposites for EOR in a carbonate oil reservoir. In their study, xanthan/magnetite/SiO 2 nanocomposites (NC), eucalyptus plant nanocomposites (ENCs), and walnut shell ones (WNC) were used and their efficiency for EOR was examined through IFT and CA measurement as well as spontaneous imbibition tests.…”
Section: Introductionmentioning
confidence: 99%